Answer:
x=7
Step-by-step explanation:
9x-9=5x+19
Combine like terms
9x-5x=19+9
4x=19+9
4x=28
x=7
Givens
Sequence 2, - 4, 8, -16, 32 ....
First term = a = 2
Problem
Find the nth term
tn = (-1 )^(n -1) * (a)^n answer or
tn = (-1)^(n - 1) * 2^n
where a is defined as the first term (it usually is given that designation).
Try a few to make sure the formula is correct
<em>n = 1</em>
t1 = (-1)^(1 - 1) * 2^1
t1 = (-1)^0 * 2
t1 = 1 * 2 = 2
<em>n =2</em>
t2 = (-1)^(2 - 1) * 2^2 = (-1)^1 * 4 = -4
Answer:
WHERE IS THE TABLES HM???
Answer:
y = -3
Step-by-step explanation:
So, first you need to plug in -4y-4 for x. So, 5(-4y-4) + 2y=34. Now, use the distributive property and now it will become -20y -20 + 2y = 34. Add like terms which would be -20y + 2y = -18y. Now the equation is -18y - 20 = 34. Now use inverse operations and add 20 to both sides. Then the equation will be -18y = 54. When you divide -18 on both sides, you get y=-3.
Hope this helps :)